2021
DOI: 10.1007/978-3-030-86304-3_10
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Gender-Based Violence: Outcomes, Challenges and Future Perspectives

Abstract: Climate change (CC) is often described as an environmental problem raising political concerns and debates but also perceived as a social human problem (Clayton 2019;Dias et al. 2020). CC presents a broadly systemic health risk, making the world more dangerous to live in, further enhancing social and psychological stress of people (Johnson 2020). Translated into extreme weather events or natural disasters, such as droughts and desertification, floods, forest fires and cyclones, CC is extremely complex and has i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The hurricanes also impeded public health efforts by damaging hospital infrastructure including potable water and cold chain equipment for vaccines ( PAHO and WHO, 2022 ). Gender-based violence, which affects household food security ( Okpara and Anugwa, 2022 ), can be impacted by changing social and economic dynamics within households as a result of both climate change ( Caridade et al, 2022 ) and the COVID-19 pandemic (Chandan et al, 2020); Honduras saw a 14% increase in reports of gender-based violence between February and May 2022 ( Fromm et al, 2022 ). Scholars have described “the three Cs” as “uneven crises” with compounding, inequitable impacts on vulnerable populations including women, lower-income households, racially/ethnically marginalized groups, and communities in climate hotspots ( Belsey-Priebe et al, 2021 ; Sultana, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The hurricanes also impeded public health efforts by damaging hospital infrastructure including potable water and cold chain equipment for vaccines ( PAHO and WHO, 2022 ). Gender-based violence, which affects household food security ( Okpara and Anugwa, 2022 ), can be impacted by changing social and economic dynamics within households as a result of both climate change ( Caridade et al, 2022 ) and the COVID-19 pandemic (Chandan et al, 2020); Honduras saw a 14% increase in reports of gender-based violence between February and May 2022 ( Fromm et al, 2022 ). Scholars have described “the three Cs” as “uneven crises” with compounding, inequitable impacts on vulnerable populations including women, lower-income households, racially/ethnically marginalized groups, and communities in climate hotspots ( Belsey-Priebe et al, 2021 ; Sultana, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study show that one of the effective preparedness components for sexual violence in natural disasters is empowering the community as well as the medical staff by increasing resilience, education, and training. In other studies, researchers have found that community knowledge is crucial to preventing sexual violence during disasters and providing the necessary resources in the event of one ( 9 , 18 , 72 , 73 ). Raising public awareness of dangerous behaviors helps in preventing sexual violence and letting those who are exposed to it know what services and treatment they should receive ( 34 , 74 - 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of work has documented the links between WASH access and gender‐based violence (Abu Sharekh, 2021; Pommells et al, 2018) and intimate partner violence (Choudhary et al, 2020; Mushavi et al, 2020). Recent work has connected water insecurity with community‐level and intra‐household conflict, and how these relationships may be shaped by regional conflict (Pearson et al, 2021) and exacerbated by climate change (Caridade et al, 2022; Mack et al, 2021). While traditional water conflict metrics have tended to be implemented at regional scales, we can learn a lot about community and household conflict through short survey modules, with additional precautions for assessing physical and sexual violence.…”
Section: Measuring Transformative Washmentioning
confidence: 99%